Environmental Impact of Foreign vs. Domestic Capital Investment in China - Boqiong Yang; Stephan Brosig; Jianguo Chen (Journal of Agricultural Economics, 2013)
We compare environmental impacts associated with incoming foreign direct investment vs. domestic capital in China. We use aggregate data on Chinese provinces' economic and pollution indicators to explore the effects of the financial origin of fixed capital. Our simultaneous models consider three prime channels through which these effects work: economic scale, sectoral composition and pollution intensity. Results show that emissions associated with foreign-financed capital are lower than with domestically financed capital for some but not all of the considered types of pollution.
Keywords: F2; Q56; Q58; 330; Domestic capital; environmental impacts; foreign direct investment; pollution emission